Exploring The Implementation of Inclusive Education in English Classroom: A Case Study - Wahyu Narendhra, Bima; Rahima, Aida; Maulana, Bintang Putra Karna; Suhada, Suhada; Setyowati, Lestari (Fakultas Ilmu Budaya, Universitas Brawijaya, 2025)
This study explores the implementation of inclusive education in English classrooms at a public senior high school in Malang, with a focus on the English teacher's instructional methods, teaching experiences, and SEN students challenges encountered in an inclusive setting. A case study design was employed, involving two SEN students and one English teacher. Data were collected through classroom observations and semi-structured interviews. The findings highlight several key points. First, the teacher taught English in three phases; pre, whilst, and post activity, occasionally provided additional support to an ADHD student when they faced difficulties. Second, no specific treatment was given for SEN students, as the teacher treated them similarly to their mainstream peers during instruction. Third, SEN students experienced various challenges, including difficulty following instructions, struggling with social interactions, issues in completing classroom assignments—either finishing too quickly but inaccurately, or having trouble in completing tasks—restlessness (such as fidgeting), and inconsistencies between oral and written performance. Overcoming these challenges require targeted interventions, including using simplified instructions, providing social skills training for SEN students, incorporating fidget tools, breaking tasks into manageable steps, and utilizing manageable oral and written assessments for SEN students.